Experimentally informed limit states and fragility curves of rocking blocks via shaking table tests - Carla Colombo; Georgios Vlachakis; Nathanaël Savalle; Anastasios I. Giouvanidis; Nuno Mendes; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2026)
This paper presents an extensive shaking table campaign conducted on free-standing rocking blocks subjected to recorded earthquakes. The campaign investigates different sources and degrees of variability in the rocking response, considering material irregularities, differences in block aspect ratios, and variability in the input ground motions. The experimental programme consists of the development of experimental incremental dynamic curves, incorporating test repetitions, thereby addressing the repeatability limitation of most experimental campaigns, resulting in a dataset of over 300 shaking table tests. The analysis of the results is organised in a three-stage framework. First, the rocking response is examined through a deterministic approach based on time-history analyses. Subsequently, a statistical evaluation is conducted to explore the experimental relationships between engineering demand parameter and selected intensity measures. Finally, the pronounced influence of various sources of uncertainty on the rocking response highlights the necessity of a probabilistic interpretation of the data, culminating in the development of experimentally informed fragility curves. This paper introduces a novel methodology for the objective identification of experimental limit states for rocking structures, proposing ranges for three response thresholds corresponding to limited rocking, moderate rocking, and near-collapse conditions that can be adopted for vulnerability assessments.

Insights on the experimental dynamic behaviour and energy losses of rocking blocks under free vibration - Carla Colombo; Georgios Vlachakis; Anastasios I. Giouvanidis; Nathanaël Savalle; Nuno Mendes; Paulo B. Lourenço (Bulletin of Earthquake Engineering, 2026)
This study focuses on the experimental response of free-standing hard limestone blocks under free vibration. The campaign includes 120 tests, varying the block’s height-to-width ratio and considering multiple specimens to account for the aleatoric variability of the phenomenon. The study offers full reconstruction of the three-dimensional free-rocking motion, giving insights into the influence of unintended geometrical asymmetries, as well as material and interface irregularities on the response. The paper revisits the experimental estimation of the angular Coefficient of Restitution (CoR) through different methodologies based on the angular velocities, potential energy, and potential and frictional energies. The results are compared with Housner’s theoretical model. Due to the sensitive nature of rocking motion, a statistical approach is employed. The findings indicate that Housner’s model provides statistically accurate predictions of energy losses for blocks of medium-to-high slenderness (i.e. with aspect ratio $$5 \le {H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} \le 10$$ while it becomes statistically inaccurate for very slender $${H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} > 10$$ and very stocky $${H \mathord{\left/ {\vphantom {H B}} \right. \kern-\nulldelimiterspace} B} < 5$$ blocks. Importantly, the study demonstrates that all three experimentally estimated CoRs statistically depend on the aspect ratio. Finally, the CoRs extracted from the potential energy and potential and frictional energies are found statistically dependent on the rocking amplitude, while the CoR extracted from the angular velocities show statistical independence. Overall, this study offers a pathway for more systematic analyses and improved predictions of energy losses during impacts.

Seismic loss and resilience assessment of single-column rocking bridges - Anastasios I. Giouvanidis; You Dong (Bulletin of Earthquake Engineering, 2020)

Nonsmooth dynamic analysis of sticking impacts in rocking structures - Anastasios I. Giouvanidis; Elias G. Dimitrakopoulos (Bulletin of Earthquake Engineering, 2017)